Thermoplastic Toughened Epoxy Networks and Their Toughening Mechanisms in Some Systems - Rutnakornpituk, Metha (Asian Health, Science and Technology Reports, 2005)
Epoxy resins have drawn a lot of attentions as construction materials in recent years due to their excellent mechanical and thermal properties. However, their brittleness is a major disadvantage which significantly limits their uses. Incorporation of thermoplastic polymers has found to overcome this drawback. Literature reviews in using various thermoplastic polymers, e.g., poly(phenylene oxide) (PPO), polysulfone (PSF) and polyetherimide (PEI), have been summarized herein. The toughening mechanisms that have been proposed and the measurement of their mechanical properties are also discussed.